Hexapod Robot Movement Control for Uneven Terrain - Prasetio, Yusuf; Widodo, Nuryono Satya (Control Systems and Optimization Letters, 2023)
Hexapod robot is a robot that has 6 legs with joints or structures that resemble insect legs. This study uses the inverse kinematic method with the aim of finding points and effectors of the robot's legs that will make the robot's legs pass through uneven obstacles such as uneven flor, stairs, bolong-bolong obstacles, bolong-non-obvious obstacles and non-objective obstacles. This inverse kinematic is accessed with the Open Cm 9.04 microcontroller to control the dynamixel servo on the robot leg. The results of testing the robot's movement using inverse kinematics have succeeded in overcoming uneven obstacles using the inverse kinematic method. For testing the stability of the robot it is still not stable enough because the mechanical part of the foot is still not precise. The conclusion of the study, from 6 trials that average and uneven obstacles were obtained in the range of 85% - 95%. The inverse kinematic method using a proximity sensor on the front of the robot, the average success that can be obtained is in the range of 80% - 90%.